Achievement-related within-school socioeconomic gaps in science subjects in China: evidence on existence, consistency, and compensation. Issue 4 (1st October 2016) - Ma, Xin; Yuan, Jing; Luo, Xingkai
ABSTRACT: Using data from the 2011 (Chinese) Student Academic Achievement Evaluation, we examined whether within-school socioeconomic gaps in science achievement exist across science subjects, how consistent they are, and whether there are relationships between school average science achievement and within-school socioeconomic gaps in science achievement. Results of multivariate multilevel analyses indicate that for both fathers and mothers within-school socioeconomic gaps in science achievement existed among schools but did not vary much across schools. School mean socioeconomic status and teacher experience were related to these gaps. Schools were strongly consistent in within-school socioeconomic gaps in science achievement across science subjects, and this consistency was independent of (robust to) student and school characteristics. The relationships between school average science achievement and within-school socioeconomic gaps in science achievement were rather weak among schools across science subjects, and the addition of school characteristics to student characteristics effectively demolished the relationships.